Asian cohort for Alzheimer's disease (ACAD) data collection: Rationale, design and validation. (31st December 2021) - Chow, Tiffany W; Reyes‐Dumeyer, Dolly; Gu, Yian; Li, Clara; Tee, Boon Lead; Lee, Haeok; Park, Van Ta; Lieu, Kevin; Lu, Anna T; Peavy, Guerry M; Hsiung, Ging‐Yuek Robin; Vogel, Briana; et al.
Abstract: Background: As the first large Alzheimer's Disease (AD) genetics cohort for Asians in the United States and Canada, the Asian Cohort for Alzheimer's Disease (ACAD) has adapted existing instruments to collect data on sex, genetics, medical history, and lifestyle risk factors. We hypothesize that any and all of these factors impact AD risk differently for Asians. Initially ACAD focuses on US and Canadian participants of Chinese, Korean, and Vietnamese ancestry. Method: ACAD's Clinical Workgroup reviewed commonly used dementia research questionnaires, including the NACC Uniform Data Set, Religious Order Study, and NIA‐Late‐Onset AD to select, and in some cases adapt, questions that are most appropriate for ACAD. A combination of AD clinical researchers and community outreach specialists reviewed the data collection packet, administration procedures, and consensus diagnosis process for cultural sensitivity without sacrificing scientific rigor to gather non‐genetic and lifestyle risk factor data. Result: We designed the ACAD Data Collection Packet (DCP) to create a friendly dialogue with participants through a socio‐culturally and linguistically sensitive 3‐part process. The DCP consists of some instruments already validated in Chinese, Vietnamese and Korean languages to screen for cognitive impairment (Cognitive Abilities Screening Instrument (CASI) and Modified Mini‐Mental State (3MS)). Part A collects origins, Mediterranean diet compliance, and Clinical Dementia Rating scores. The self‐administered Part B uses an adaptation of the Rush Cognitive Activity Questionnaire on early‐life enrichment. Part C structures the collection of medical history and cognitive testing with CASI vs 3MS, the Common Objects Memory Test, Category (not Letter) Fluency, and the 15‐item Clock Drawing Task. This assessment is designed to be administered either remotely or face to face. Conclusion: Over the next year, we will pilot the ACAD Data Collection Packet, to set a community standard for dementia screening among Asian Americans and Canadians that can support data harmonization across epidemiological studies. While ACAD translation accommodates Chinese, Korean, and Vietnamese at this stage, we look forward to implementing additional major Asian languages.